The Potent Inhibitory Effect of β-D-Mannuronic Acid (M2000) as a Novel NSAID with Immunosuppressive Property on Anti-Cyclic Citrullinated Peptide Antibodies, Rheumatoid Factor and Anti-dsDNA Antibodies in Patients with Rheumatoid Arthritis - Ahmadi, Hossein; Jamshidi, Ahmad R.; Mahmoudi, Mahdi; Cuzzocrea, Salvatore; Fattahi, Mohammad J.; Barati, Anis; Rehm, Bernd H. A.; Matsuo, Hidenori; Mirshafiey, Abbas (Current Drug Discovery Technologies, 2017)
Objective: To investigate the inhibitory effect of β-D-mannuronic acid (M2000) on anti-cyclic citrullinated peptide antibodies (anti-CCP), rheumatoid factor (RF), antidouble strand DNA (anti-dsDNA) and acute phase reactants in rheumatoid arthritis (RA) patients. Methods: The study included 40 patients with RA who had an inadequate response to conventional therapy (identifier: IRCT2014011213739N2). The patients were permitted to continue the conventional therapy excluding NSAIDs. 21 of them were treated orally by M2000 at a dose of 500 mg twice daily for 12 weeks and the others did not. Serum samples were collected at baseline, 4 weeks and 12 weeks after treatment and were tested for the serum level of anti-CCP and anti-dsDNA antibodies using enzyme linked immunosorbent assay. The serum level of RF and C-reactive proteins (CRP) was determined by the immunoturbidimetric assay, respectively. Results: At baseline, all patients in the M2000 treated group and the control group were positive for anti-CCP, RF. moreover, 4 of 21 (19%) in the M2000 treated group and 2 of the 19 (10.5%) patients in the control group were positive for anti-dsDNA antibodies, respectively. The serum levels of anti-CCP, RF and anti-dsDNA were decreased significantly after M2000 therapy (p<0.001, p<0.001 and p<0.001, respectively). The reduction in the level of anti-CCP was positively correlated with disease activity, swollen joint count and CRP. Furthermore, the level of inflammatory markers ESR and CRP decreased significantly after M2000 therapy (p<0.001 and p<0.004, respectively). Conclusion: M2000 shows inhibitory effect on anti-CCP, RF, anti-dsDNA antibodies and acute phase reactants in RA patients.
Keywords: RF